When "embedded" means "stuck": Moderating effects of job embeddedness in adverse work environments - Allen, David G; Peltokorpi, Vesa; Rubenstein, Alex L (Journal of applied psychology, 2016)
Job embeddedness is predominately assumed to benefit employees, work groups, and organizations (e.g., higher performance, social cohesion, and lower voluntary turnover). Challenging this assumption, we examined the potentially negative outcomes that may occur if employees are embedded in an adverse work environment-feeling "stuck," yet unable to exit a negative situation. More specifically, we considered two factors representing adverse work conditions: abusive supervision and job insecurity. Drawing from conservation of resources theory, we hypothesized that job embeddedness would moderate the relationship between these conditions and outcomes of voluntary turnover, physical health, emotional exhaustion, and sleep quality/quantity, such that employees embedded in more adverse environments would be less likely to quit, but would experience more negative personal outcomes. Results from two independent samples, one in Japan (N = 597) and one in the United States (N = 283), provide support for the hypothesized pattern of interaction effects, thereby highlighting a largely neglected "dark side" of job embeddedness. (PsycINFO Database Record